2023
DOI: 10.1039/d3lc00387f
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic membraneless microbial fuel cells: new protocols for record power densities

Abstract: In addition to offering a promising approach for niche applications in environmental sensing and portable power sources, microfluidic microbial fuel cells (MFCs) can also accelerate the development of mainstream energy...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 64 publications
(127 reference statements)
0
6
0
Order By: Relevance
“…The normalized power densities may be significantly higher than reported above. While normalizing by projected electrode area is typical in microfluidic MFCs literature, we have recently shown that not all of the electrode surface area is useful for EAB growth in side-by-side electrodes [5]. Rather, as previous authors have demonstrated, outputs can be limited by bottlenecks in the electrolyte contact area between the anode and cathode chambers [32,33].…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…The normalized power densities may be significantly higher than reported above. While normalizing by projected electrode area is typical in microfluidic MFCs literature, we have recently shown that not all of the electrode surface area is useful for EAB growth in side-by-side electrodes [5]. Rather, as previous authors have demonstrated, outputs can be limited by bottlenecks in the electrolyte contact area between the anode and cathode chambers [32,33].…”
Section: Discussionmentioning
confidence: 88%
“…No overshoot was observed at any time, indicating that the EAB was not stressed by oxygen accumulation or from exposure to ferricyanide crossover from the catholyte co-flow stream. We credit this to the improved fluid delivery system, which avoided crossover of the catholyte to the anode chamber [5]. From an analysis of the polarization curves at 50 h in Figure 2a, several indicators showed that performance was improved as the EAB matured.…”
Section: Electrochemical Performance and Resistances With Timementioning
confidence: 93%
See 3 more Smart Citations